Aberrant Cyclization Affords a C-6 Modified Cyclic Adenosine 5′-Diphosphoribose Analogue with Biological Activity in Jurkat T Cells - Moreau, Christelle (American Chemical Society, 2012)
[Image: see text] Two nicotinamide adenine dinucleotide (NAD(+)) analogues modified at the 6 position of the purine ring were synthesized, and their substrate properties toward Aplysia californica ADP-ribosyl cyclase were investigated. 6-N-Methyl NAD(+) (6-N-methyl nicotinamide adenosine 5′-dinucleotide 10) hydrolyzes to give the linear 6-N-methyl ADPR (adenosine 5′-diphosphoribose, 11), whereas 6-thio NHD(+) (nicotinamide 6-mercaptopurine 5′-dinucleotide, 17) generates a cyclic dinucleotide. Surprisingly, NMR correlation spectra confirm this compound to be the N1 cyclic product 6-thio N1-cIDPR (6-thio cyclic inosine 5′-diphosphoribose, 3), although the corresponding 6-oxo analogue is well-known to cyclize at N7. In Jurkat T cells, unlike the parent cyclic inosine 5′-diphosphoribose N1-cIDPR 2, 6-thio N1-cIDPR antagonizes both cADPR- and N1-cIDPR-induced Ca(2+) release but possesses weak agonist activity at higher concentration. 3 is thus identified as the first C-6 modified cADPR (cyclic adenosine 5′-diphosphoribose) analogue antagonist; it represents the first example of a fluorescent N1-cyclized cADPR analogue and is a new pharmacological tool for intervention in the cADPR pathway of cellular signaling.